Protection Forest: A New Dimension for Biodiversity Conservation, Sustainable Forest Management and Livelihood Improvement - Lamsal, Prakash (The Initiation, 2011)
Protected areas have greater role in the biodiversity conservation, sustainable forest management and livelihood improvement. Government of Nepal has different provisions for the management of such areas. Centralized conservation concept has broadened to participatory and people centred approach. Landscape approach is the latest one in this field. There are various benefits of the declaration of the protected forest, and initiatives are also being taken from the Governmental sector, but along with that several negative impacts are also being witnessed. A clear strategy is needed in this regard. This paper talks about the development of the participatory approach, government initiatives and positive and negative impacts and the challenges ahead. DOI: http://dx.doi.org/10.3126/init.v4i0.5543 The Initiation Vol.4 2011 111-114